فاعلية المحبة بين الأثرة والإيثار دراسة أدبية نقدية لتنازر بُنى الوعي ــ رواية (بنات الغابة) لـ سالم العوكلي أُنموذجاً (Comprehensive Journal of Science, 2026)
This study interrogates the efficacy of love not as a romantic theme, but as a resistant act and a dramatic rupture against dominant norms. It adopts a critical approach that refuses to separate author from text, viewing Banat al-Ghaba(Daughters of the Forest) as an existentially costly experience in which Salem Al-Awkali unites with his own self through a piercing honesty, veiled behind the mask of the protagonist. In doing so, he conveys truths that may reflect his own private “forest,” challenging the mechanisms of control and repression that seek to domesticate human existence.The analysis traces the strict dialectic between selfishness and altruism, transforming the novel into a battlefield of competing structures of consciousness—sometimes clashing, sometimes converging—while resisting the coercive forces imposed by dominant systems. Al-Awkali’s artistic sincerity propels him toward altruism and truth, declaring allegiance to innate freedom against the falsity and constraints of the city. Thus, the novel transcends the boundaries of reality into broader spaces, moving beyond reproductive or materialist bourgeois consciousness toward a creative awareness.The study concludes that Al-Awkali’s vision of love functions as a formal declaration of liberation. The dramatic weaving of the narrative converts a hidden personal experience into a critical force that destabilizes ossified structures, elevating the writer as a seer who confronts silence with words. He assumes full responsibility, indifferent to the reader’s level of engagement—whether instinct-driven, bourgeois, or creatively receptive. Between selfishness and altruism, Al-Awkali positions himself as a knight in a forest of entangled emotions, leaving the choice to the reader to embrace a universal love that signifies goodness and unconditional giving.
Keywords: Dialectics of consciousness structures ، Altruism، Selfishness، Love، Innate freedom، Creative awareness